Parametric investigation of Urban Heat Island dynamics through TEB 1D model for a case study: Assessment of adaptation measures. (May 2018) - Reder, Alfredo; Rianna, Guido; Mercogliano, Paola; Castellari, Sergio
Highlights: Parametric study on alterations in temperature between urban areas and their surroundings using TEB model. Parametric study on the capability of some local adaptation measures in countering the UHI magnitude using TEB model. Implementation of urban configurations and local adaptation measures to make well-adapted and climate-resilient cities. Adaptation measures may reduce significantly the temperature on the town elements during the daylight hours. Green roof prevents the radiative cooling, increasing the roof night temperature and contributing to the night UHI. Abstract: At present, the urban population has to cope with the effects caused from Urban Heat Island (UHI), poor air quality and increased frequency and/or intensity of extreme weather and climate events. The expected increase of these extremes in areas of the planet and the way to adapt to them has emphasized the need to investigate in detail the climate of the cities. Local vulnerability and risk assessments, supported by using regional climate models at very high resolution, are key to support development and implementation of effective local adaptation measures to make well-adapted and climate-resilient cities, i.e. more sustainable ones. This study aims to provide some quantitative information on the effectiveness of main local adaptation measures to reduce the magnitude of UHI, in terms of temperature and energy fluxes. The investigation was conducted by adopting the TEB 1D model for the Toulouse city case-study. Different urban configurations and adaptation measures have been considered in the model set up. The results confirm that different adaptation measures may reduce the temperature on the town elements during the daylight hours; among the different measures, the green roof prevent the radiative cooling, increasing the roof night temperature and contributing to the night UHI.